Symposium 8: Elaborating Collaborative Interactions in Networked Learning: A Multi-Method Approach - Lally, Vic; de Laat, Maarten (Proceedings of the International Conference on Networked Learning, 2002)
This paper, which reports work in progress, considers the methodological difficulties of investigating learning and tutoring processes of an advanced learning community, within a collaborative virtual professional development environment. Results are presented from content analysis. NVivo was used to assist the coding process with two schemas. The first schema attempts to probe the social co-construction of knowledge by analysing the social, cognitive and metacognitive contributions to an online learning event. In the second schema the presence and patterns of tutoring processes within the group is investigated. These patterns of group and individual activity for both learning and tutoring are then analysed. The interactions between these are also considered. In conclusion, consideration is given to the prospects for this type of approach as a means of adding value to our understandings of the complexity of the relationship between tutoring and learning in virtual professional development environments. The methodological issues of using complimentary methods of analysis to probe participant dynamics and non-expressed thinking are also considered. Papers: Deciphering Individual Learning Processes in Virtual Professional Development Vic Lally and Maarten Delaat Network and content analysis in an online community discourse Maarten Delaat Squaring the Circle: Triangulating Content and Social Network Analysis with Critical Event Recall Vic Lally